Ex Vivo Inhibition of Platelet Aggregation in Patients with Severe Limb Arteriopathy Treated with BAY U3405, a Specific IX A2 Receptor Antagonist - Bellucci, S; Kedra, W; Groussin, H; Jaillet, N; Molho-Sabatier, P; Andreassian, B; Tobelem, G (Thrombosis and Haemostasis, 1994)
A double-blind, placebo-controlled randomized study with BAY U3405, a specific thromboxane A2 (TX A2) receptor blocker, was performed in patients suffering from severe stade II limb arteriopathy. BAY U3405 or placebo was administered in 16 patients at 20 mg four times a day (from day 1 to day 3). Hemostatic studies were done before therapy, and on day 2 and day 3 under therapy. On day 3, BAY U3405 was shown to induce a highly statistically significant decrease of the velocity and the intensity of the aggregations mediated by arachidonic acid (56 ± 37% for the velocity, 58 ± 26% for the intensity) or by U46619 endoperoxide analogue (36 ± 35% for the velocity, 37 ± 27% for the intensity). Similar results were already observed on day 2. By contrast, such a decrease was not noticed with ADP mediated platelet aggregation. Furthermore, plasma levels of betathrombo-globulin and platelet factor 4 remained unchanged. Peripheral hemodynamic parameters were also studied. The peripheral blood flow was measured using a Doppler ultrasound; the pain free walking distance and the total walking ability distance were determined under standardized conditions on a treadmill. These last two parameters show a trend to improvement which nevertheless was not statistically significant. All together these results encourage further in vivo studies using BAY U3405 or related compounds on a long-term administration.